2001
DOI: 10.1023/a:1011111322376
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET for detection of pulmonary metastases from malignant primary bone tumors: Comparison with spiral CT

Abstract: There seems to be a superiority of spiral CT in the detection of pulmonary metastases from malignant primary bone tumors as compared with FDG-PET. Therefore, at present a negative FDG-PET cannot be recommended to exclude lung metastases. However, as specificity of FDG-PET is high, a positive FDG-PET result can be used to confirm abnormalities seen on thoracic CT scans as metastatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(96 citation statements)
references
References 17 publications
5
80
0
11
Order By: Relevance
“…These findings are in accordance with those of former studies showing that the sensitivity of PET alone is low and inferior to that of spiral CT in detecting pulmonary metastases and may be attributable to respiration movements during emission acquisition (23,24). The PET/CT technique offers both the high sensitivity of PET in the detection of osseous and soft-tissue lesions (23,25) and the high sensitivity of CT in the detection of lung metastases within a single examination.…”
Section: Organ-specific Analysessupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are in accordance with those of former studies showing that the sensitivity of PET alone is low and inferior to that of spiral CT in detecting pulmonary metastases and may be attributable to respiration movements during emission acquisition (23,24). The PET/CT technique offers both the high sensitivity of PET in the detection of osseous and soft-tissue lesions (23,25) and the high sensitivity of CT in the detection of lung metastases within a single examination.…”
Section: Organ-specific Analysessupporting
confidence: 91%
“…A total of 124 new foci detected by CT (20%) were not seen by PET alone; 65% of the new foci detected by CT were located in the lungs. These findings are in concordance with those of earlier PET studies in patients with Ewing tumor, which showed a low sensitivity of PET for the detection of pulmonary metastases (24,25,27). Although none of the new foci detected by CT were of physiologic origin, 55% were scored as probably or definitely benign.…”
Section: Additional Foci Detected By Ctsupporting
confidence: 91%
See 1 more Smart Citation
“…Most orthopaedic oncologists suggest axial imaging at the primary tumor site (either CT scanning or MRI) along with a chest CT scan at defined intervals to determine the presence or absence of pulmonary metastasis. Positron emission tomography (PET), particularly with radiolabeled (18)F2-deoxy-2-fluoro-d-glucose (FDG), has been described as a useful staging adjunct as a result of its ability to provide an in vivo metabolic tumor profile [9]. Its use for surveillance after tumor resection is less well described [4,6,9] but offers the potential to correlate potentially concerning radiographic findings with metabolic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET), particularly with radiolabeled (18)F2-deoxy-2-fluoro-d-glucose (FDG), has been described as a useful staging adjunct as a result of its ability to provide an in vivo metabolic tumor profile [9]. Its use for surveillance after tumor resection is less well described [4,6,9] but offers the potential to correlate potentially concerning radiographic findings with metabolic behavior. Standardized uptake values (SUVs) of less then 2.0 are generally Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%